Treatment of Nerve Injury and Entrapment Neuropathy - Hirasawa, Yasusuke (Springer Japan, 2002)
Peripheral nerve injury and entrapment neuropathy often are complicated by injury to adjacent tissue such as bone, joints, blood vessels, and tendons. Clinicians who provide primary care in these areas require extensive knowledge of methods for treating wounds and nerve injuries. The most important element in the treatment of peripheral nerve injury is appropriate surgical repair or functional reconstruction; postoperative physical and occupational therapy are also necessary. This book summarizes current topics in Japan and other countries in the field of surgical nerve repair, including selection of treatment methods for peripheral nerve paralysis, practical issues in surgery, and aspects of postoperative care. The importance of evidence-based medicine is emphasized, with appropriate therapy decided on the basis of objective data. The book has a broad appeal to include general clinicians, clinical trainees, and allied health-care professionals